The role of interfacial excess charge in the reversibility of proton and hydroxide solvation in electrocatalysis and bipolar membranes - Carlos Gomez Rodellar; Jody Druce; José Maria Gisbert-González; Francisco Sarabia; Beatriz Roldan Cuenya; Sebastian Z. Oener (Proceedings of the National Academy of Sciences, 2026)
The desolvation and recombination of protons and hydroxides in the bulk is one of the fastest reactions known to mankind. The very existence of an increased activation barrier at heterogenous interfaces reflects a key component of interfacial chemistry. Here, we use the recombination and generation of solvated H + and O H - at bipolar (membrane) interfaces as a test reaction to understand how interfacial excess charge impacts the electrochemical reversibility of inner-sphere reactions. We observe that excess charge, that is independent of the overpotential, primarily increases the activation energy. In contrast, when the overpotential changes the excess charge asymmetrically between the forward and reverse direction, water formation ( H + + O H - → H 2 O ) and water dissociation (WD) ( H 2 O → H + + O H - ) can switch between outer-sphere-type kinetics and distinct compensation effects between the Arrhenius pre-exponential factor and activation energy. Finally, observe that the charge transfer coefficients that quantify the overpotential dependence of the proton and hydroxide transfer through the extended hydrogen bond network are dependent on the excess charge, too, and can take values that are distinctly different from those obtained in electron-transfer reactions. The results are very important to understand how interfacial solvation and ion transfer reactions are modulated by the ubiquitous presence of excess charge across electro- and bio- and even geochemistry. Further, the results help outline the very conditions for fast electrocatalyst kinetics and describe when and how they might break down.